Group size and conformity in charitable giving: Evidence from a donation-based crowdfunding platform in Japan - Shusaku Sasaki (Osaka University, Institute of Social and Economic Research (ISER), 2017)
This study examines relationships between the size of the majority and donor conformity by empirically investigating the impacts of multiple earlier donations on the amount that a subsequent donor contributes to JapanGiving, a donation-based crowdfunding platform. The platform's webpage displays the amounts of the preceding five donations in chronological order. Using data for 9,989 donations and exploring the model propounded by Smith et al. (2015), we construct variables to explain information a donor sees on the webpage. The main variables are the modal amount among the preceding five donations and their appearance along the sequence. Dynamic panel analyses suggest that when the two most recent donations are identical, a subsequent donor is likely to match the immediately preceding donation. The likelihood further increases when the number of the most recent continuous modal donations increases. We discuss that our findings connect economic studies of charity and social psychology studies of conformity and could aid effective fundraising by charities.
Keywords: D64; H41; C99; 330; Charitable giving; Conformity; Fundraising management; Crowdfunding; Natural experiment; Online dataset